2023
DOI: 10.3390/cancers15143750
|View full text |Cite
|
Sign up to set email alerts
|

Early Age of Onset Is an Independent Predictor for a Worse Response to Neoadjuvant Therapies in Sporadic Rectal Cancer Patients

Abstract: The incidence of rectal cancer (RC) is increasing in the population aged ≤ 49 (early-onset RC-EORC). EORC patients are more likely to present with locally advanced disease at diagnosis than late-onset RC (LORC; aged ≥ 50) patients. As a consequence, more EORC patients undergo neoadjuvant therapies. The response to treatment in EORC patients is still unknown. This study aims to explore the effect of age of onset on the pathological response to neoadjuvant therapies in sporadic locally advanced RC (LARC) patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…Between the younger-onset and later-onset cohorts, there were no statistically significant differences in pCR rates (12% and 15%, respectively), with similar 5-year overall survival rates (86% and 84%, respectively). This contradicts earlier findings which hypothesized early-onset rectal cancer responds differently to TNT [36,37]. Additional data is needed to assess whether age or tumor characteristics associated with early-onset disease are risk factors for poor response to TNT, and therefore, not ideal for WW approaches.…”
Section: The Benefit Of Tnt Based On Demographicscontrasting
confidence: 58%
See 3 more Smart Citations
“…Between the younger-onset and later-onset cohorts, there were no statistically significant differences in pCR rates (12% and 15%, respectively), with similar 5-year overall survival rates (86% and 84%, respectively). This contradicts earlier findings which hypothesized early-onset rectal cancer responds differently to TNT [36,37]. Additional data is needed to assess whether age or tumor characteristics associated with early-onset disease are risk factors for poor response to TNT, and therefore, not ideal for WW approaches.…”
Section: The Benefit Of Tnt Based On Demographicscontrasting
confidence: 58%
“…Other studies have shown age is not associated either positively or negatively with pCR [50]. A hypothesis for future research to explore is if younger patients have other tumor and patient characteristics, including more aggressive features, that are not responsive to treatment [48] or if younger patients are more likely to receive maximum and aggressive treatment [36] with no actual differences in pCR rate based on age.…”
Section: Patient Demographicsmentioning
confidence: 96%
See 2 more Smart Citations
“…Data from the literature regarding the pathological complete response rate (pCR) after neoadjuvant treatment in rectal cancer in relation with the age of the patients are contradictory. Some authors present results that show a better response to treatment in the case of young people [44], whereas in other studies the results are worse [45,46]. Possible mechanisms to explain these differences are given by means of molecular and clinical characteristics.…”
Section: Discussionmentioning
confidence: 95%